FORMULATION AND EVALUATION OF HERBAL SOAP BY USING AZADIRACTAINDICA AND OCIMUM TENUIFLORUM - Bhati, Pooja; Tomer, Kirti; Mundada, Saurabh; Choursiya, Surbhi; Carpenter, Garima; Ojha, Vijay; Panwar, Mangal Singh; Jain, Amit Kumar (South Eastern European Journal of Public Health, 2025)
Azadirachta indica and Ocimum tenuiflorum leaf and bark extracts were used to create a herbal soap and hand sanitizer. Ayurvedic cosmetics are sometimes referred to as herbal cosmetics because most herbal supplements are based on many botanical substances that have been used for many years in traditional or folk medicine. The natural content of the herbs has no negative effects on human health. of the many botanical ingredients that are now on the market. Cosmetics by themselves are insufficient to proper care of skin and body parts; a variety of chemical toxins and microorganisms found in the atmosphere may result in chemical infection and damage to skin.The Azadirachta indica, or neem, tree is well-known throughout the world for its many medicinal uses. Studies have shown that neem leaves and their constituents have anti-inflammatory, antihyperglycemic, antiulcer, antimalarial, antifungal, antibacterial, antimutagenic, and anticarcinogenic effects. The purpose of this research study was to assess the effects of neem & tulsi leaf extracts that were aqueous, ethanolic, and ethyl acetate. Neem leaf and seed were found to be beneficial against certain dermatophytes, and tulsi demonstrates antifungal and antiviral activity in the herbal soap formulation.